Determinants of UAE Voters' Preferences for Federal National Council Candidates. (September 2015) - Yaghi, Abdulfattah; Antwi‐Boateng, Osman
Abstract: The purpose of this study was to explore the voting behavior in United Arab Emirates by asking 1, 800 citizens about which criteria they used to vote for a particular candidate in the past Federal National Council elections. Using descriptive statistics, the study showed that although patron‐client networks played a role in voter's preferences — as existing literature about Middle East voters' behavior has established — they were superseded by personal attributes and the impact of candidates' campaigns. Emiratis voted for candidates based on three groups of factors, namely: 1) personal characteristics of the candidate including: public speaking skills, political experience, age, gender and educational level; 2) impact of a candidate's campaign including electoral promises and content of the campaign; and 3) patron‐client networks including having personal and kinship relationship with candidate. The study showed that religious, political, and personal appearance factors were insignificant.